Grounded theory approach in sermon analysis of sermons on poverty and directed at the poor as listeners - H. J. C. Pieterse (Acta Theologica)
The grounded theory approach is implemented in analysing sermons on poverty and directed at the poor as listeners. This is an abductive approach in the paradigm of social constructionism as developed by Cathy Charmaz in Sociology. I am applying this method of empirical analysis to sermons, in this case sermons on poverty with Matthew 25:31-46 as sermon text. In this article, I am going to discuss the place of grounded theory in qualitative research and the application of Charmaz’s approach to it in homiletics. The process of sermon analysis in its different phases will be discussed as well as the interaction of this bottom-up theory with existing homiletic theories in relation to the research topic. The goal is to update our knowledge contextually in the interaction between praxis and theory with a view to preaching in our context of poverty.